The Relationship Between Professionalism of Christian Religious Education Teachers and Interest in Learning Christian Religious Education for Middle School Students in Donokerto Surabaya - Apri Tarigan; Daniel Ari Wibowo (Sekolah Tinggi Teologi Injili Indonesia Surabaya, 2022)
The objectives of this research are: The author wants to know Is there a relationship between the professionalism of Christian Religious Education teachers and students' interest in learning Religious Christian education. Professional Relations of Religious Education Teachers Christian (X) with an interest in learning Christian Religious Education of SMP Donokerto Surabaya students (Y) there is a relationship. From the results of the simple regression statistical test between the variables of Professionalism of Christian Religious Education Teachers (X) with Interest in Learning Christian Religious Education of Donokerto Junior High School students Surabaya, the results obtained the finding of ryx value, is 0.701 and is positive. This means, that the magnitude of the relationship between the Professionalism of Christian Religious Education Teachers with interest in learning Christian Religious Education students of Junior High School students Donokerto Surabaya is 70.1%, then the relationship between variables X and Y is included in the category of high relationship.